GEOCHEMICAL CHARACTERISTICS AND THERMAL MATURITY OF THE UPPER DEVONIAN ROCKS (DNIEPER-DONETS BASIN) ACCORDING TO ROCK-EVAL PYROLYSIS DATA (EXPLORATION DRILLING) - KARPENKO, Ivan; ISCHENKO, Ihor; KARPENKO, Oleksii (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. In the Dnieper-Donets Basin (DDB), Devonian deposits are a very interesting object of hydrocarbon system research – from the initial stage of hydrocarbon generation to the stage of formation of oil and gas deposits. The presence of sedimentary layers enriched with scattered organic matter determines the oil and gas generation potential of the deposits. The article presents the results of laboratory studies of Upper Devonian rocks performed on the Rock-Eval pyrolytic tool in order to assess their thermal maturity and degree of hydrocarbon generation. Methods. Laboratory studies were carried out by the method of pyrolysis of rock samples (Rock-Eval) with the determination of a number of parameters that allow for the assessment of thermal maturity, the type of organic matter (kerogen) and the coefficient of organic matter transformation. Data processing was performed using the methods of mathematical statistics. Results. An important result of the research is the established regularity that shales and limestones with an increased content of organic carbon (TOC) of the Famennian layer from between-salt strata in this part of the DDB are already in the active phase of oil generation and belong to oil-source rocks. Precisely in this part of the Dnieper-Donets depression the main explored reserves of liquid hydrocarbons in the Eastern region are concentrated. Conclusions. Generalized conclusion based on the results of the above studies: most samples of shales (argillites) and limestones have quite high concentrations of organic carbon; the thermal maturity of the rocks for 63 % of the samples corresponds to the "oil window"; all four types of kerogen are present in the rocks; the best oil-generating properties are characteristic of shales from between-salt strata; also, these shales have the maximum degree of realization of the generating potential TRI – more than 0.3 at depths of 4,700 m. The results of the above studies indicate that the shales and limestones of the Frasnian and Famennian layers from the studied deposits can be considered as potential oil-source rocks.
Keywords: Devonian; kerogen; pyrolysis; sourse rock; hydrocarbons; Dnieper-Donetsk basin